Nitric and nitrous oxide fluxes from intensifying crop agriculture in the seasonally dry tropical Amazon–Cerrado border region. Issue 2 (10th May 2021) - Huddell, Alexandra; Neill, Christopher; Maracahipes‐Santos, Leonardo; Cerri, Carlos Eduardo Pellegrino; Menge, Duncan
Abstract: Rapid expansion and intensification of crop agriculture in the tropics may accelerate ecosystem losses of reactive nitrogen (N). We quantified emissions of nitric oxide (NO) and nitrous oxide (N2 O) in forest, single‐cropped soybean [ Glycine max (L.) Merr.], and N‐fertilized double‐cropped soybean–maize ( Zea mays L.) at three N fertilizer levels within the largest area of recent cropland expansion on earth, in the Amazon and Cerrado biomes in Brazil. The NO emissions were 2.1 kg N ha ‒1  yr ‒1 in forest, 0.6 kg N ha ‒1  yr ‒1 in soybean, and 1.3 kg N ha ‒1  yr ‒1 in soybean–maize. The N2 O fluxes were <1.1 kg N ha ‒1  yr ‒1 across all land uses. As fertilization levels increased from 80 to 160 kg N ha −1  yr ‒1 in soybean–maize double‐cropped sites, NO emissions increased from 0.6 to 6.7 kg N ha −1 mo ‒1 in the month immediately after fertilization, but N2 O emissions only increased from 0.6 to 1.8 kg N ha −1 mo ‒1 . These results indicate that NO emissions do not increase when forests are converted to croplands under current fertilization levels, and that NO will respond more strongly than N2 O fluxes to increases in fertilizer applications. Our findings suggest that if N fertilization rates in the region were increased, NO fluxes could increase rapidly. Core ideas:  Nitric oxide fluxes were measured across three land uses in the southern Amazon.  Nitric oxide fluxes from forest were significantly higher than in soybean fields.  Increases in nitrogen fertilizer caused large nitric oxide fluxes in soybean–maize.  Nitrous oxide fluxes across all land uses were <1.1 kg N ha ‒1  yr ‒1 .